What Motivates Malaysians to Engage in Social Commerce Shopping Intention? - Wan Rasyidah Wan Nawang; Raja Azhan Raja Mamat; Intan Fatimah Anwar (Universiti Malaysia Sabah (UMS), 2026)
Tier 3- Indexed by MyCite